ANALISIS BREAK EVEN POINT SEBAGAI DASAR PERENCANAAN LABA PRODUK BOLU PISANG BLONDE PETAK PADA TOKO ROTI NEKO-NEKO BAKERY & CAKE CABANG PEMATANG SIANTAR - Siregar, Liper; Ervina , Nelly; Purnama Sari, Eka; Eka Putri, Debi; Nilam Cahyariani, Vivi (JURNAL EKONOMI PERJUANGAN, 2023)
The objectives of this research are to determine out the picture of total sales, fixed costs, variable costs, selling prices, and break even points as a basis for profit planning for banana blonde sponge products plots and to find out the break even point analysis as a basis for profit planning for banana blonde plot sponge products. The research design used in this research is field research and literature research. The analytical techniques used in this study are quantitative descriptive analysis and inductive analysis. The types of data used are qualitative data and quantitative data. The data sources used in this study are primary data and secondary data. Data collection techniques are carried out by documentation and interview methods. The results of the research can be concluded as follows Break even point of banana blonde sponge product plots from 2017 to 2021 in units and the rupiah has increased. The level of margin of safety for banana blonde plot products from 2017 to 2021 has increased. Keywords: Break Even Point Analysis, Profit Planning